HUBUNGAN ANTARA PERUBAHAN KADAR HS-CRP DENGAN FUNGSI KOGNITIF PADA STROKE ISKEMIK - Sumanti, Betsi; Hexanto, Hexanto; Widiastuti, Widiastuti (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
Ã‚Â Ã‚Â Ã‚Â ASSOCIATION BETWEEN ALTERED HS-CRP LEVELS ANDÃ‚Â  COGNITIVE FUNCTION OF ISCHEMIC STROKE PATIENTSABSTRACTIntroduction:Ã‚Â The incidence of cognitive impairment in acute ischemic stroke patients is increasing. The mechanism of the inflammatory effect, such as Ã‚Â elevated hs-CRP level, a Ã‚Â non-specific inflammatory marker Ã‚Â sensitive to chronic inflammation due to hypoperfusion as well other vascular risk, is thought to have an effect on cognitive function.Aims:Ã‚Â To determine the relationship of cognitive function changes in acute phase of ischemic stroke with hs-CRP level changes on day 3 and day 7 after onset.Methods:Ã‚Â This was a cross sectional study of 31 first-timer ischemic stroke patients who met inclusion and exclusion criteria. The level of hs-CRP was checked on the 3rd day and 7th day after onset, while MoCA-Ina was assessed on the 7th day after onset. Cognitive disturbance was considered if MoCA <26. Analyses was done using SPSS 2.0Results:Ã‚Â The average onset of day 3 Hs-CRP concentration was 0.66 (0.12-16.67)mg/dl and the onset of day 7 was 5.455 (0.14-17.34)mg/dl. The mean change of hs-CRP level between 3 day and 7 day after onset was -0,16 (-3.32-4.95). There was a significant correlation between elevated hs-CRP levels on day 3 and day 7 after onset with cognitive function of acute ischemic stroke patients.Discussion:Ã‚Â There was a significant correlation between elevated hs-CRP levels on day 3 and day 7 after onset with cognitive function of acute ischemic stroke patients.Keyword:Ã‚Â Acute ischemic stroke, hs-CRP, MoCA-Ina scoresABSTRAKPendahuluan:Ã‚Â Insidens penurunan fungsi kognitif pada pasien stroke iskemik akut semakin meningkat. Hal ini diduga dipengaruhi oleh mekanisme efek inflamasi, meliputi peningkatan kadarÃ‚Â high sensitive-C reactive proteinÃ‚Â (hs-CRP), salah satu penanda inflamasi non-spesifik yang sangat sensitif pada inflamasi kronis, akibat hipoperfusi maupun karena risiko vaskuler lainnya.Tujuan:Ã‚Â Mengetahui hubungan perubahan fungsi kognitif pasien stroke iskemik fase akut dengan perubahan kadar hs-CRP hari ke-3 dan hari ke-7 setelah awitan.Metode:Ã‚Â Studi potong lintang terhadap penderita stroke iskemik pertama kali yang memenuhi kriteria inklusi dan eksklusi. Dilakukan pemeriksaan kadar hs-CRP hari ke-3 dan hari ke-7 setelah awitan dan MoCA-Ina pada hari ke-7 setelah awitan. Fungsi kognitif dinyatakan terganggu jika MoCA-Ina <26. Analisis data menggunakan program SPSS 22.0.Hasil:Ã‚Â Didapatkan rerata kadar Hs-CRP hari ke-3 setelah awitan adalah 0,66 (0,12-16,67)mg/dl dan hari ke-7 setelah awitan adalah 5,455 (0,14-17,34)mg/dl. Dengan rerata perubahan kadar hs-CRP awitan hari ke-3 dan awitan hari ke-7 adalah -0,16 (-3,32-4,95). Didapatkan hubungan yang bermakna antara perubahan kadar hs-CRP hari ke-3 setelah awitan dan hari ke-7 setelah awitan dengan fungsi kognitif pasien stroke iskemik akut.Kesimpulan:Ã‚Â Didapatkan hubungan yang bermakna antara peningkatan kadar hs-CRP pada hari ke-7 dan kadar hari ke-3 dengan fungsi kognitif pasien stroke iskemik akut.Kata kunci:Ã‚Â hs-CRP, MoCA-Ina, stroke iskemik akutÃ‚Â